Integrated Production Planning for Shoulder Leader Pin at PT XYZ - Alifah Almas; Nadila Puspita Tri Handayani; Muhammad Naufaldi Rasyid; Hikmal Abrar; Niken Parwati; Widya Nurcahayanty Tanjung (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2026)
Accurate production planning plays a critical role in balancing market demand and a company’s production capacity. PT XYZ, a manufacturing company producing industrial spare parts, faces production planning issues for its shoulder leader pin product due to the absence of a structured demand forecasting system. This study aims to develop an integrated production planning framework by applying demand forecasting, Master Production Schedule (MPS), Rough-Cut Capacity Planning (RCCP), and Material Requirement Planning (MRP). One year of historical demand data was analyzed using the Double Moving Average (DMA) and Double Exponential Smoothing (DES) methods of Brown. Forecasting accuracy was evaluated using Mean Absolute Percentage Error (MAPE), with the DMA method achieving a lower MAPE of 3.10%, indicating better accuracy than DES Brown. The selected forecasting results were used as input for the development of the MPS. RCCP analysis demonstrated that the available production capacity at all workstations was sufficient to meet the planned production requirements throughout the planning horizon, without requiring additional capacity. Furthermore, MRP was conducted to determine the quantity and timing of raw material procurement for SUJ2 steel with a one-period lead time. The MRP results indicate that material requirements can be fulfilled precisely in each period without excess inventory. Overall, the implementation of an integrated production planning system enables PT XYZ to improve planning accuracy, align production capacity with demand, and enhance operational efficiency.